2020
DOI: 10.1111/jnc.15011
|View full text |Cite
|
Sign up to set email alerts
|

Muscone suppresses inflammatory responses and neuronal damage in a rat model of cervical spondylotic myelopathy by regulating Drp1‐dependent mitochondrial fission

Abstract: Cervical spondylotic myelopathy (CSM) is a common cause of disability with few treatments. Aberrant mitochondrial dynamics play a crucial role in the pathogenesis of various neurodegenerative diseases. Thus, regulation of mitochondrial dynamics may offer therapeutic benefit for the treatment of CSM. Muscone, the active ingredi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…These findings were also supported by those previously reported on muscone, the active ingredient of musk, which has been reported to exert antidementia (Liu et al, 2017), anticerebral ischemia (Surinkaew et al, 2018), and neuroprotective effects (Zhou et al, 2020). These activities and its underlying mechanisms are involved in promoting cell proliferation, ameliorating the loss of cell viability, preventing mitochondrial membrane potential collapse, lactate dehydrogenase, Ca 2+ overload, ROS generation, and reducing the release of inflammatory factors, such as IL-1β, TNF-α, prostaglandin E2, and myeloperoxidase (Liu et al, 2017;Surinkaew et al, 2018;Zhou et al, 2020). Wei et al (2012) and Zhang et al (2020) reported that muscone can inhibit apoptosis via inhibiting expression of caspase 8 and Fas in the cortex and stimulate neural stem cells proliferation transforming them into neurons in ischemia/reperfusion rats.…”
Section: Discussionsupporting
confidence: 90%
“…These findings were also supported by those previously reported on muscone, the active ingredient of musk, which has been reported to exert antidementia (Liu et al, 2017), anticerebral ischemia (Surinkaew et al, 2018), and neuroprotective effects (Zhou et al, 2020). These activities and its underlying mechanisms are involved in promoting cell proliferation, ameliorating the loss of cell viability, preventing mitochondrial membrane potential collapse, lactate dehydrogenase, Ca 2+ overload, ROS generation, and reducing the release of inflammatory factors, such as IL-1β, TNF-α, prostaglandin E2, and myeloperoxidase (Liu et al, 2017;Surinkaew et al, 2018;Zhou et al, 2020). Wei et al (2012) and Zhang et al (2020) reported that muscone can inhibit apoptosis via inhibiting expression of caspase 8 and Fas in the cortex and stimulate neural stem cells proliferation transforming them into neurons in ischemia/reperfusion rats.…”
Section: Discussionsupporting
confidence: 90%
“…The symptoms of CSM are changeable and the etiologies are complex, resulting in difficult to explain its natural course [2]. Although the development of CSM is relatively slow, it could lead to spinal cord dysfunction and seriously affect the quality of patients' life, even lead to disability [2,3]. At present, surgical decompression is the main treatment of CSM, which aims to remove compression of the spinal cord, so as to effectively restore the physiological curvature of the cervical spine and the corresponding spinal canal capacity and shape.…”
Section: Backgroundsmentioning
confidence: 99%
“…The dominant-negative mutant of Drp1, as well as siRNA-mediated silencing of Drp1, could reduce apoptosis in Q111/0 cells in Huntington’s disease ( Costa et al, 2010 ). By inhibiting Drp1 activation, mitochondrial debris and ROS can be reduced, and neuronal damage can be alleviated ( Zhou et al, 2020 ). Using propofol to treat oxidation-injured neurons could reduce the expression of Fis1 and increase the expression of Mfn1, maintaining normal levels of these two proteins, thus reducing the expression of apoptotic proteins in neurons and alleviating neuronal damage induced by hypoxia ( Zhang H. S. et al, 2020 ).…”
Section: The Role Of Mitochondrial Dynamics In Brain Injury After Ischemic Strokementioning
confidence: 99%